Reproductive biology of Phymaturus Spectabilis (Liolaemidae): females skip reproduction in cold and harsh environments of Patagonia, Argentina - Boretto, Jorgelina Mariela (2014)
Herein, we describe the reproductive biology of Phymaturus spectabilis, a lizard species that inhabits rocky outcrops in cold and arid environments of the Patagonian steppe of Argentina. We studied male and female reproductive cycles, mean annual reproductive output, allometric changes during ontogeny, and sexual dimorphism, mainly with a non-invasive methodology used for the first time in Argentina. We corroborated results from this non-invasive method with data from euthanized individuals through observation, classification, and measurement of the female reproductive tract and ovaries and through examination of the histology of testicles and epididymis in males. The presence of males with spermatozoa in the epididymis from early spring and gravid females from mid spring shows that mating, ovulation, and egg development occur at the beginning of the activity season. Parturition occurs in midsummer to two offspring. Our finding that half of the adult females were in a non-reproductive condition during the entire reproductive season, simultaneously with vitellogenic or gravid females, demonstrates that not all of the adult females in this population reproduce every year. Females exhibited an annual to biennial cycle, sometimes skipping a year of reproduction, while males exhibited an annual cycle. Phymaturus spectabilis show the common pattern of low mean annual reproductive output found in the genus Phymaturus. The low frequency of reproduction and the low mean annual reproductive output are risk factors for this species. These life-history traits, together with its microendemic character (as it is restricted to an area of 70 km2 of fragmented and rocky plateaus in the poorly protected steppe of Patagonia Argentina), mean that this species is of concern.